Hepatitis B virus reactivation in cancer patients with positive Hepatitis B surface antigen undergoing PD-1 inhibition. Issue 1 (21st November 2019) - Zhang, Xuanye; Zhou, Yixin; Chen, Chen; Fang, Wenfeng; Cai, Xiuyu; Zhang, Xiaoshi; Zhao, Ming; Zhang, Bei; Jiang, Wenqi; Lin, Zuan; Ma, Yuxiang; Yang, Yunpeng; et al.
Abstract : Background: Hepatitis B virus (HBV) reactivation is a serious complication in patients with cancers and HBV infection undergoing immunosuppressant treatment or chemotherapy. However, the safety of anti-programmed cell death (PD) -1 and anti-programmed cell death-ligand 1 (PD-L1) therapy in these patients is unknown because they were excluded from clinical trials of immunotherapy. Methods: This retrospective cohort study involved consecutive hepatitis B surface antigen (HBsAg) -positive cancer patients who were referred to Sun Yat-sen University Cancer Center and received an anti-PD-1/PD-L1 antibody between January 1, 2015 and July 31, 2018. The primary end point was the rate of the occurrence of HBV reactivation. Results: In total, 114 eligible patients were included, among whom 90 (79%) were male, and the median (range) age was 46 (16–76) years. Six patients (5.3%) developed HBV reactivation, occurring at a median of 18 weeks (range, 3–35 weeks) from the commencement of immunotherapy. Among these patients, all of them had undetectable baseline HBV DNA; one had prophylactic antiviral therapy while five did not; four were positive for Hepatitis B e antigen while the other two were negative. At reactivation, the median HBV DNA level was 3.89 × 10 4 IU/mL (range, 1.80 × 10 3 –6.00 × 10 7 IU/mL); five had HBV-related hepatitis and one exhibited increasing HBV DNA level without alanine transaminase elevation. No HBV-related fatal events occurred. The lack of antiviral prophylaxis was the only significant risk factor for HBV reactivation (odds ratio, 17.50 [95% CI, 1.95–157.07], P = .004). Conclusions: HBV reactivation occurs in a subset of HBsAg-positive cancer patients undergoing anti-PD-1 or anti-PD-L1 immunotherapy. Regular monitoring of HBV DNA and antiviral prophylaxis are advised to prevent this potentially fatal complication.